Being and becoming : a field approach to psychology - Combs, Arthur W. (Arthur Wright), 1912-1999 (Springer Pub. Co., 1999)
Dr. Combs updates his groundbreaking Field Theory of personality. This model grows out of Carl Rogers' ideas on client-centered therapy and has long been a major influence on theories of psychotherapy and personality within the humanistic and phenomenological traditions. Here Dr. Combs ties field psychology to the paradigm shifts in biophysical sciences, and so provides a unifying frame of reference for all branches of psychology. His concise approach to the topic make this book of practical interest to students, clinical psychologists and counselors, as well as academics teaching upper-level or graduate courses in personality and on therapeutic techniques.